Mechanisms of Implementation of Innovative Activity in The Educational System - J. Ro‘ziev (Web of Journals Publishing, 2023)
In this article, based on the reforms implemented in the field of education in Uzbekistan, the innovative organization of education, achieving high efficiency through it, the specific features of the introduction of innovative education, all the necessary for young people to become qualified personnel socio-philosophical analysis of the constructive essence of providing resources, satisfying the moral needs of the society, expanding its material capabilities.
Keywords: education, innovation, traditional and innovative education, educational technology, object, methodological consciousness, reason, outlook, substance.